Workspace Analysis of Auxiliary Slag Cleaning Device of TBM based on Monte Carlo Method - Jia Liangfei; Ma Chaofeng; Liu Kai (Jixie chuandong)
Aiming at the current rock burst problems encountered in hard rock excavation construction，a set of six-degree-of-freedom automatic excavation equipment which can replace the current artificial slag and can work well in a narrow working space is designed.The specific design is on the basis of the traditional excavating machine，two telescopic arm structures and a swing arm structure are added，and each rod length and each joint variable are set by kinematically modeling the mechanical arm.The design overcomes the problem of the small amount of operable space and the protection of the supporting I-beam for the pre-supported tunnel，and expands the working space of the conventional excavation equipment in a narrow space.The overall structure of the excavation equipment and the kinematics modeling process are expounded.By using the characteristics of Monte Carlo method in random number application，the workspace of this device is simulated.At the same time，the joint parameters are reversed and verified.The results are in line with the expected joint operating range.The slag cleaning device can improve the working efficiency of cleaning the gravel caused by rock burst，and can reduce the construction cost of the hard rock tunneling.